Técnicas de contagem de leucócitos e parâmetros hematológicos para espécies nativas de peixes. - Faria, Bráulio Pêgo de (2016)
The lack of closed technological packages for some fish species that are economically important in Brazil,calls the necessity of more haematological studies for these species.In order to obtain a precise and trustful result in a blood test, techiniques that are not adapted from other species but created and tested specifically need to be researched. The aim of this dissertation was to determine haematological parameters values for some native fish species and test the blood analysis techinique for red blood cells count, leucocytes count and thrombocytes count. The experiment was performed between February and June of 2015 in the Laboratório de Nutrição e Produção de Espécies Ornamentais (LNPEO) from the Instituto Federal do Espirito Santo –CampusAlegre. The total of 175 animals with the age of 6 to 8 months were used, within 5 different species 35 Tambaquis (Colossoma macropomum), 35Pacus (Piaractus mesopotamicus), 35 Tambacu (híbridos, P. mesopotamicusx C. macropomum), 35 Acarás (Geophagus brasiliensis) e 35 Traíras(Hoplias malabaricus).. The fishes were captured in the pounds of the aquiculture sector, anesthetised with clove oil(25mg/L), being the blood collected by puncture of the ventral vessel at the caudal peduncle of the animal, using 3 ml sterile syringes and 25x7mm needles with EDTA 10%. The White blood cell count from the samples was performed, using the Natt and Herrick (1952) methodology, the Pitombeira and Martins (1966) methodology and the Porfirio-Silva methodology.Other variables analyzed were Hematocrit, Red blood cells count, White Blood Cells count, Special Granulocytic cell, Neutrophils, Lymphocytes, Monocytes, eosinophils and thrombocytes. The analyzed variables from the red series in this experiment, showed lower variation coefficient when compared to the white series. Parameters variation among species is something to be expected, due to the genotypic and phenotypic variation.It wasconcluded that the blood parameters evaluated from the target species of this study, showed homogeneityof values, which can help in the future, with the comparasion between healthy and unhealthy animals. And also that the “Porfirio-Silva” technique was the most indicated to perform the total leukocytes count in fishes.Therefore, more studies about new leukocytes counting techniques should be encouraged in order to facilitate the closing of technological packages for commercial produced species with poor technology.